Interaction of diet and habitat predicts Toxoplasma gondii infection rates in wild birds at a global scale. Issue 7 (12th April 2020) - Wilson, Amy G.; Lapen, David R.; Mitchell, Gregory W.; Provencher, Jennifer F.; Wilson, Scott
Abstract: Aim: Free‐ranging wildlife are valuable sentinels for zoonotic, multi‐host pathogens, and new insight into parasite transmission patterns is possible through a macroecological approach. Toxoplasma gondii is a protozoan capable of infecting all warm‐blooded animals, including humans, primarily through a free‐living oocyst and/or tissue cyst life stage. Anthropogenic disturbance is facilitating the spread of T. gondii, making it crucial to understand the general ecological and life‐history drivers of T. gondii infections in wild birds, which are important intermediate hosts. Our goal was to determine how habitat (terrestrial versus aquatic), dietary trophic level and scavenging behaviour influence the prevalence of T. gondii infection in wild birds at a global scale. Location: Global. Time period: 1952–2017. Major taxa studied: Birds. Methods: Our analysis used the serological, bioassay and molecular prevalence data of T. gondii in avian species compiled from 81 studies conducted worldwide and encompassing 24, 344 individuals from 393 avian species from 84 families. Results: We showed that at a global scale, trophic level and habitat interacted significantly to influence T. gondii prevalence in avian intermediate hosts. In the terrestrial environment, T. gondii prevalence increased with trophic level, consistent with predominant tissue cyst transmission. The highest prevalence was in terrestrial omnivores, which might reflect their synanthropic foraging behaviour. In aquatic species, prevalence was more consistent across trophic levels, but high prevalence in aquatic herbivores and insectivores reflects significant waterborne exposure to oocysts. Contrary to our predictions, generalized scavenging per se was not associated with increased prevalence. Main conclusions: This study highlights the value of comparing pathogen prevalence among multiple ecological guilds and ecosystem types for a more comprehensive understanding of the epidemiology of generalist pathogens, such as T. gondii . Increased effort is needed to reduce T. gondii spillover from the domestic cat cycle into wildlife populations.